O uso do espaço aeroportuário pela espécie Coragyps atratus. Estudo de caso: Aeroporto Estadual Comandante Rolim Adolfo Amaro - SBJD - Glanso, Claudia Militão Berbert (Universidade Federal de São Carlos, 2018)
The danger to aviation safety due to birds has drawn attention for many years. In Brazil, more than 8,000 wildlife collisions were recorded between 2011 and 2015, in addition to a significant increase in wildlife sightings at airports or their immediate surroundings. This increase may be due to the fact that aerodromes are naturally attractive to the fauna, especially birds, because they are large open areas, protected from predators and humans, and have water and food sources for many species. The management of bird risk, in order to be efficient, must rely on local actions of data collection and observation of the attractive fauna-problem factors such as the black-headed vulture (Coragyps atratus), widely distributed throughout Brazil. Thus, the present study aimed to understand the use of the airport space by the C. atratus species, as well as the attraction factors that keep it frequently present inside the SBJD airport site and propose management measures aiming to reduce the potential risk of collisions. For this purpose, the species was monitored for 14 months to identify the most critical points. The analysis, through Kernel Maps, indicated that having restaurants inside the airport site interferes with the presence density of the species, and its higher frequency in the rainy/hot period. A Fauna Risk Management Program was also developed with the objective of managing the risk of collision between animals and aircraft operating at and around the aerodrome, through procedures and operational routines.
Keywords: Avaliação de riscos ambientais; Aves; Focos de atração; Aeroportos; Environmental risks assessment; Birds; Focus of attraction; Airports; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS